Nfatc1 Directs the Endocardial Progenitor Cells to Make Heart Valve Primordium - Wu, Bingruo (2013)
Heart valves arise from the cardiac endocardial cushions located at the atrioventricular canal (AVC) and cardiac outflow tract (OFT) during development. A subpopulation of cushion endocardial cells undergoes endocardial to mesenchymal transformation (EMT) and generates the cushion mesenchyme, which is then remodeled into the interstitial tissue of the mature valves. The cushion endocardial cells that do not undertake EMT proliferate to elongate valve leaflets. During EMT and the post-EMT valve remodeling, endocardial cells at the cushions highly express nuclear factor in activated T-cell, cytoplasmic 1 (Nfatc1), a transcription factor required for valve formation in mice. In this review, we present the current knowledge of Nfatc1 roles in the ontogeny of heart valves with a focus on the fate decision of the endocardial cells in the processes of EMT and valve remodeling.